Integrated Omics Reveals the Orchestrating Role of Calycosin in Danggui Buxue Tang, a Herbal Formula Containing Angelicae Sinensis Radix and Astragali Radix, in Inducing Osteoblastic Differentiation and Proliferation - Kwan, Kenneth K L; Wong, Tin Yan; Yu, Anna X D; Dong, Tina T X; Lam, Henry H N; Tsim, Karl W K (Frontiers in Pharmacology, 2021)
Systems biology unravels the black box of signaling pathway of cells; but which has not been extensively applied to reveal the mechanistic synergy of a herbal mixture. The therapeutic efficacy of a herbal mixture having multi-target, multi-function and multi-pathway is the niches of traditional Chinese medicine (TCM). Here, we reported an integrated omics approach, coupled with the knockout of active compound, to measure the regulation of cellular signaling, as to reveal the landscape in cultured rat osteoblasts having synergistic pharmacological efficacy of Danggui Buxue Tang (DBT), a Chinese herbal mixture containing Angelicae Sinensis Radix and Astragali Radix. The changes in signaling pathways responsible for energy metabolism, RNA metabolism and protein metabolism showed distinct features between DBT and calycosin-depleted DBT. Here, our results show that calycosin, within DBT mixture, can orchestrate the osteoblastic functions and signaling pathways of the entire herbal mixture. This finding reveals the harmony of herbal medicine in pharmacological functions, as well as the design of drug/herbal medicine formulation. The integration of systems biology can provide novel and essential insights into the synergistic property of a herbal mixture, which is a key in modernizing TCM.